Glocal Wisdom in Earthquake Mitigation and Education for Sustainable Development - Hanan Zaki Alhusni; Binar Kurnia Prahani; Titin Sunarti; Madlazim Madlazim (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: This study systematically analyses how glocal wisdom — the integration of local and global knowledge — supports earthquake mitigation and education for sustainable development (ESD). It identifies research patterns, key themes, and gaps in the linkage between cultural wisdom and disaster risk reduction and sustainability education. Method: A Systematic Literature Review (SLR) based on the PRISMA protocol was conducted using the Scopus database. From an initial 66,648 records (2015–2025), 15 peer-reviewed articles were selected through multi-stage filtering based on year, subject area, document type, language, and open-access criteria. Data were analysed using bibliometric mapping and thematic content analysis. Results: Four dominant themes emerged: (1) local knowledge in structural mitigation, (2) glocal wisdom in community-based education, (3) ESD integration models, and (4) policy and implementation gaps. The increase in studies from 2020 to 2023 reflects growing global interest in integrating indigenous knowledge into modern disaster education systems. Novelty: This research redefines glocal wisdom as a core epistemological foundation for sustainable and disaster-resilient education. By combining bibliometric and qualitative analyses, this study proposes a new integrative framework that links traditional knowledge, scientific innovation, and pedagogy to advance ESD and disaster literacy.